Nasal pack after septoplasty - Ali , Muna .M.; Albargathi , Haleemah. A.; Belkhair, Hussain. A. (Scientific Journal of University of Benghazi, 2022)
Background: Septoplasty is one of the commonest procedures done in ENT department in which bleeding necessitate packing. Nasal packing is painful and it may be the fearful step of surgery by the patient, her we will study the need of nasal packing after this procedure. Aim: The aim is to determine the need for an anterior nasal pack (A.N.P.) after septal surgery Patients and methods: This study is a prospective comparative study that was carried out in Al -Hawari Center for 26 months. Eighty-eight patients were operated on and divided randomly on whether or not to apply a nasal pack. Research data were collected from each patient. Forty-four cases were packed with Vaseline gauze or merocele and the remaining 44 cases were not. Results: A total of 88 subjects were included with 44 in each group. the mean age of septal surgery cases was 28.1 years of age; standard deviation (S D) =7.4. The minimum and maximum ages were 18 and 48 years respectively. For the primary outcome of the study (post-operative bleeding, headache and pain), there were no statistically significant differences between the two groups (P-values 0.15, 0.39 and 0.38 respectively). However, The overall complications in both groups show a p-value of 0.02 which is a statistically significant difference Conclusion: In this small series study, we noticed no significant benefit of nasal packing. On the other hand, it increases the patients suffering by causing complete nasal obstruction, pain and headache. It increases the length of the hospital stay and so the overall cost. Therefore, nasal packing may be of use only in selected cases where bleeding tendencies are more. In a cleanly-performed surgery that does not cause bleeding, nose packing is not needed.